2018
DOI: 10.5194/nhess-2018-26
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards impact-based flood forecasting and warning in Bangladesh: a case study at the local level in Sirajganj district

Abstract: Abstract. Impact-based forecasting and warning services aim to bridge the gap between producers and users of warning information by connecting and increasing synergies between the components of effective early warning systems. We tested qualitatively whether a warning message based on colour codes is understandable and useful to trigger risk mitigation 15 actions at the local level in the flood-exposed communities of Rajapur and Ghorjan unions in Sirajganj district, Bangladesh.With a community-based approach f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…The flood warning system adopted in Niamey is based on the four-colour classification of risk scenarios associated with critical hydraulic levels and potential impacts. The fourcolour coded classes currently used respond to the international standards (International Organisation for Standardisation-ISO 22324:2015) [37]. Thresholds are based on the river water level (H) at the hydrometric station as follows: Yellow: H = 530 cm; Orange: H = 580 cm; Red: H = 620 cm.…”
mentioning
confidence: 99%
“…The flood warning system adopted in Niamey is based on the four-colour classification of risk scenarios associated with critical hydraulic levels and potential impacts. The fourcolour coded classes currently used respond to the international standards (International Organisation for Standardisation-ISO 22324:2015) [37]. Thresholds are based on the river water level (H) at the hydrometric station as follows: Yellow: H = 530 cm; Orange: H = 580 cm; Red: H = 620 cm.…”
mentioning
confidence: 99%
“…The results of the study are discussed herein according to the indicators identified by Sai et al [19] for steering each of the four components of effective EWS (See Table A1 in Appendix A).…”
Section: Discussionmentioning
confidence: 99%
“…They are associated with warning content (the core of the message is the color), with the colored hydrometric staff gauges (qualitative gauging staffs) installed along the river, as well as information panels in the villages indicating priority actions to be taken. We adopted the four color-coded classes currently used by different countries (i.e., United Kingdom-the Met Office; EU-Meteoalarm, Philippine-Pegasa, Italy-Protezione Civile, India Meteorological Department) [19] and responding to the international standards (International Organization for Standardization -ISO 22324:2015). The classes are related to discharge, return periods and impacts on the main riverine settlements according to the classification, as described by Massazza et al [27]-essentially, green stands for the normal condition, meaning a no-impact scenario, yellow (Stationary Return Period 10 years) stands for minor impacts, orange (Stationary Return Period 30 years) stands for significant impacts and red (Stationary Return Period 100 years) stands for severe impacts.…”
Section: Dissemination and Communication: Stakeholders' Consultationmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent survey of the development of operational forecasting systems for floods (Perera et al, 2020) shows that in many countries and river basins good progress has been made, though such progress is often limited in least developed countries, hampered by a lack of monitoring networks as well as human and technical capacities. These also often focus on large space and time scale riverine floods, which have attracted most attention of the flood forecasting, warning and response research community (Alfieri, et al, 2018, Kauffeldt, et al, 2015, Sai, et al, 2018. Flash floods, in contrast, occur at smaller spatial and temporal scales, resulting in severe damage to infrastructure and the environment, and are more deadly than riverine floods (Jonkman, 2005).…”
Section: Introductionmentioning
confidence: 99%